2018
DOI: 10.1002/adma.201706707
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystals with Interfacial Ordering that Enhances Responsiveness to Chemical Targets

Abstract: The development of stimuli-responsive materials suitable for use in wearable sensors is a key unresolved challenge. Liquid crystals (LCs) are particularly promising, as they do not require power, are light-weight, and can be tuned to respond to a range of targeted chemical stimuli. Here, an advance is reported in the design of LCs for chemical sensors with the discovery of LCs that assume parallel orientations at free surfaces and yet retain their chemoresponsiveness. The resulting LC-based sensors are more se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 35 publications
(10 reference statements)
0
50
0
Order By: Relevance
“…Finally, we should mention the work conducted by Nayani et al [ 133 ] In this work, it was demonstrated that the response and sensitivity to gas analytes can be improved substantially by customizing the properties of the employed LC system. The authors synthesized a nitrile‐based LC mixture that assumes a planar configuration at the LC/air interface, contrary to the propensity for a homeotropical arrangement exhibited by cyanobiphenyl LCs, yet it maintains its chemoresponsiveness upon deposition on a metal‐cation functionalized surface (in this study, La 3+ perchlorate).…”
Section: Functional Liquid Crystal Materialsmentioning
confidence: 95%
“…Finally, we should mention the work conducted by Nayani et al [ 133 ] In this work, it was demonstrated that the response and sensitivity to gas analytes can be improved substantially by customizing the properties of the employed LC system. The authors synthesized a nitrile‐based LC mixture that assumes a planar configuration at the LC/air interface, contrary to the propensity for a homeotropical arrangement exhibited by cyanobiphenyl LCs, yet it maintains its chemoresponsiveness upon deposition on a metal‐cation functionalized surface (in this study, La 3+ perchlorate).…”
Section: Functional Liquid Crystal Materialsmentioning
confidence: 95%
“…In contrast, films of nematic 5CB supported on surfaces decorated with Ni(ClO 4 ) 2 and subsequently exposed to humid Cl 2 , exhibited no measurable orientational response (Figure , black curve; Supporting Information, Figure S6). Additional discussion of the origin of the sigmoidal shape of the response curve evident in Figure a is given in the Supporting Information …”
Section: Methodsmentioning
confidence: 99%
“…Small molecules are another type of flexible substance used in fabricating flexible sensors. [ 261 ] By molecular modifications, small‐molecule materials can present an acceptor–donor–acceptor characteristic, which has demonstrated promising application potentials on fabricating flexible electronic devices. Kim et al [ 262 ] reported their fabrication of flexible ambipolar FETs using different electron‐accepting functional groups (dicyanovinyl, cyanorhodanine, and cyanoindanone, INCN) to modify oligothiophene–phenylene molecules.…”
Section: Strategies Toward the Optimization Of F‐fet Sensorsmentioning
confidence: 99%